If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4 + -1a) + -2(a + -4) = -10a + -2a (4 * 4 + -1a * 4) + -2(a + -4) = -10a + -2a (16 + -4a) + -2(a + -4) = -10a + -2a Reorder the terms: 16 + -4a + -2(-4 + a) = -10a + -2a 16 + -4a + (-4 * -2 + a * -2) = -10a + -2a 16 + -4a + (8 + -2a) = -10a + -2a Reorder the terms: 16 + 8 + -4a + -2a = -10a + -2a Combine like terms: 16 + 8 = 24 24 + -4a + -2a = -10a + -2a Combine like terms: -4a + -2a = -6a 24 + -6a = -10a + -2a Combine like terms: -10a + -2a = -12a 24 + -6a = -12a Solving 24 + -6a = -12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12a' to each side of the equation. 24 + -6a + 12a = -12a + 12a Combine like terms: -6a + 12a = 6a 24 + 6a = -12a + 12a Combine like terms: -12a + 12a = 0 24 + 6a = 0 Add '-24' to each side of the equation. 24 + -24 + 6a = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 6a = 0 + -24 6a = 0 + -24 Combine like terms: 0 + -24 = -24 6a = -24 Divide each side by '6'. a = -4 Simplifying a = -4
| 4x-(30-x)+25=80 | | 15+4x+60=11x+12 | | 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b | | -17=m+71 | | 126=3p | | 1/3r-5=6 | | X*(x-5)=126 | | a+3b+5c=30000 | | 5r(r-7)=0 | | 3t-8=-7t | | 12x+1+10x=133 | | 2*x*y=48 | | 8/2H=8 | | 10-4x=11-x*3 | | 2q=-6q-8 | | 3x^3+37x-84=0 | | 10-4c=11-x*3 |